TECHNOLOGICAL ASPECTS OF PROCESSING OF EDIBLE MUSSELS,CLAMS AND CRABS 1:SPOILAGE DURING DURING ICE STORAGE - CHINNAMMA, p L; CHAUDHURY, 0, R.; PILLAI, V K (Fishery Technology, 2025)
Rate and pattern of spoilage of some of the economically important edible species of shell fishes viz; Mytilus edulis (Mussel), Villorita cornucopia (Clam), Neptunus pelagicus (Crab) and Scylla serrala (Crab) have been discussed in this communication. Chemical indices used for objective evaluation of quality were water extractable nitrogen (WEN), non protein nitrogen (NPN), free oe-amino nitrogen ( o<:-NH N), lycogen, lactic acid and inorganic phosphorus in addition to the subjective test . No significant difference in the spoilage pattern orthe species during ice storage was observed and these species could be preserved in ice in organoleptically acceptable condition upto 8 days, 9 days,Â· 8 days and 11 days respectively,